An assessment of the physicochemical characteristics and essential oil composition of Mentha longifolia (L.) Huds. exposed to different salt stress conditions - Singh, Ruby; Ahmed, Sajad; Luxmi, Savita; Rai, Garima; Gupta, Ajai Prakash; Bhanwaria, Rajendra; Gandhi, Sumit G. (Frontiers in Plant Science, 2023)
Salt stress adversely influences growth, development, and productivity in plants resulting in a limitation on agriculture production worldwide. Therefore, this study aimed to investigate the effect of four different salts i.e., NaCl, KCl, MgSO4, and CaCl2 applied at various concentrations of 0, 12.5, 25, 50, and 100 mM on Physico-chemical properties and essential oil composition of M. longifolia. After 45 days of transplanting, the plants were irrigated with different salinity levels at 4 days intervals for 60 days. The resulting data revealed a significant reduction in plant height, number of branches, biomass, chlorophyll content, and relative water content with rising concentrations of NaCl, KCl, and CaCl2. However, MgSO4 poses toxic effects less than other salts. Proline concentration, Electrolyte leakage, and DPPH inhibition (%) increase with increasing salt concentrations. At lower-level salt conditions, had a higher essential oil yield and GC-MS analysis reported 36 compounds in which (-)- carvone and D- limonene cover the most area by 22-50 % and 45-74 % respectively. The expression analyzed by qRT-PCR of Limonene (LS) and Carvone (ISPD) synthetic genes has synergistic and antagonistic relations in response to salt treatments. To conclude, it can be said that lower levels of salts enhanced the production of essential oil in M. longifolia, which may provide future benefits commercially and medicinally. In addition to this, salt stress also resulted in the emergence of novel compounds in essential oil in which future strategies are needed to identify the importance of these compounds in M. longifolia.